Effects of Recognition and Motivation to Teaching Personnel at Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Recognition and motivation are two important factors that can significantly affect theperformance of teaching personnel. This study aims to explore the effects of recognition andmotivation on teaching personnel in terms of their loyalty, commitment to work, and overallperformance. Recognition and motivation are crucial aspects of organizational success.Recognizing and awarding the teaching personnel for their hard work, dedication, andachievements can improve overall performance. Motivated teaching personnel are moreproductive, engaged, and committed to their work, resulting in higher levels of motivation.The result shows the findings of the study. The three variables in the part of effects ofrecognition are all interpreted as highly motivated with their respective overall weightedmeans of performance (3.63), engagement (3.72), and commitment (3.65). The effects ofrecognition on motivation also show that in terms of loyalty (3.48), productivity (3.73), andresponsibility (3.73), their respective overall weighted means are all interpreted as highlymotivated. The study shows that most of the respondents are within the age range of 41years old and above, are female, and are currently employed full-time. The majority of themhave 4-6 years of teaching experience in BCP, and most of them are from BSBA andBSEntrep. It also reveals that there is no significant relationship between the effects ofrecognition in terms of performance, engagement, and commitment and the effects ofrecognition on motivation in terms of loyalty, productivity, and responsibility of teachingpersonnel.The researchers also suggested prioritizing the teaching personnel engagement, promotingper-department recognition at the end of the semester, and recognizing work anniversarydates. At the end of the study, the researchers crafted guidelines to enhance the recognitionof the school and improve the motivation of the teaching personnel.
Keywords: Business Administration